Comparative Analysis of Body Composition Results Obtained by Air Displacement Plethysmography (ADP) and Bioelectrical Impedance Analysis (BIA) in Adults - Radosław Smolik; Martyna Gaweł; Dominika Kliszczyk; Natalia Sasin; Kacper Szewczyk; Magdalena Górnicka (Applied Sciences)
Body composition assessment provides clinical and scientific information about health, including the metabolic risks associated with low or high body fat. The aim of the study was to (i) compare the agreement of the results of the body fat percentage from the air displacement plethysmography (ADP)—BOD POD and bioelectrical impedance analysis (BIA) method—InBody 770; (ii) compare the agreement of the classification of central obesity risk in young adult, healthy females and males using data from manual measurement of waist circumference (WC) and BIA analysis. The Bland–Altman plots were used to determine the clinical agreement between BIA, ADP, and various anthropometric measurements (ADP and anthropometry were utilized as reference techniques to compare variables estimated from BIA). Finally, 203 participants enrolled in this study. We found low agreement (Bland–Altman index: 6.4%) in body fat content (%BF) and Fat Mass Index between results from ADP and BIA methods. The InBody 770 analyzer revealed an underestimation in %BF for the total group and for males. The low agreement was also observed when comparing WC measured manually versus estimated by BIA, as well as with waist-to-hip ratio (WHR). Moreover, demonstrated systematic bias and/or proportionate bias between BIA and ADP indicate that these devices cannot be used interchangeably. WC should be measured manually, especially in females.